OPTIMALISASI DEEPL TRANSLATE UNTUK MENINGKATKAN MOTIVASI DAN MINAT BELAJAR BAHASA INGGRIS PADA SISWA - Yunita, Devi; Isnaeni, Resti; Purnaningsih, Pari (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Pamulang University as a leading campus in the IT field through this activity can provide free training or workshops that will improve the ability to use the application. This community service aims to increase students' motivation and interest in learning English through the use of advanced translation technology, DeepL Translate. In this digital era, mastering English is certainly the most important thing, but many students have difficulty and lack of motivation in learning it. DeepL Translate, with its accurate and contextual translation capabilities, can be an effective tool to help students understand English texts well. The program will be implemented with a series of workshops and training for students in Vocational High Schools. Participants will also be introduced to the features of DeepL Translate and taught how to use it effectively in the English learning process. In addition, there will be a practical session where students can apply the use of DeepL Translate in various English assignments. The participants of this training are around 20 - 30 students who are all students of SMK YPUI Parung. It is hoped that through this activity, students will experience an increased understanding of English materials, which in turn will increase their motivation and interest in learning this language. Evaluation of the activity will be conducted through pre and post training surveys, as well as direct observation of student performance in English lessons. Keywords: PKM, Motivation and Interest in Learning, Language Learning Technology, DeepL Translate